Dampak Psikologis Fatherless pada Remaja dan Implikasinya dalam Konseling Islam: Systematic Literature Review - Avinka Eliza Prana Handayani; Yogi Damai Syaputra; Monalisa Monalisa (Journal of Society Counseling, 2026)
The phenomenon of fatherlessness, or the absence of a father figure in a child's life, has become an increasingly important issue in developmental psychology due to its impact on adolescents' emotional, social, and personality development. This study aims to analyze the psychological effects of fatherlessness and examine its implications for Islamic counseling. Using a qualitative approach, this research employed a Systematic Literature Review (SLR) method on relevant scholarly articles published between 2017 and 2025, retrieved from Google Scholar and SINTA databases through the Publish or Perish application. The findings indicate that the absence of a father significantly contributes to anxiety, low self-esteem, difficulties in interpersonal relationships, and weak self-control among adolescents. However, resilience factors influenced by social support and the internalization of positive values were also identified. Furthermore, Islamic counseling approaches that integrate psychological and spiritual dimensions, such as dhikr and self-reflection, have the potential to support the emotional recovery of fatherless adolescents. This study highlights the importance of developing holistic and integrative counseling services to promote the psychological well-being of fatherless adolescents.